KOMPARASI POLA SPASIAL KONDISI TERUMBU KARANG TAMAN NASIONAL KARIMUNJAWA - M Munasik; Andy Ahmad Romadhoni; Muhammad Helmi (Jurnal Kelautan, 2021)
ABSTRACTComparative studies on the percentage of coral reef substrate cover have been carried out in 3 (three) management zones (protection zone, utilization and Non-MPA) Karimunjawa National Park (KNP). The Manta Tow broadscale coral reef assessment method was applied to the north side of Bengkoang Island and the south side of Cemara Besar Island (protection zone), southern side of Bengkoang Island and northern side of Cemara Besar Island (utilization zone) and Non-MPA (Seruni Island) to observe live coral cover, dead coral, coral rubble and soft coral. Substrate cover variations from 10-12 towing (track length 200m) from each side of the island have formed a spatial pattern of coral reef conditions. Furthermore, the condition of the coral reefs was confirmed using the UPT (Underwater Photo Transect) detailed assessment method with one station on each side of the island. The results showed that there were differences in the spatial pattern of coral reef conditions as indicated by significant differences in the percentage of live coral cover, dead coral, rubble and coral lifeform among management zones of the KNP. The condition of coral reefs of the MPA is better and has a higher diversity of coral species than Non-MPA of the Karimunjawa National Park. The spatial pattern of coral reef conditions can be used as an indicator of disturbances in the coral reef ecosystem and can be used for periodic analysis of coral reef monitoring data in conservation areas.Keywords: spatial pattern, coral reef condition, manta tow, underwater photo transect, Karimunjawa National Park.ABSTRAKStudi perbandingan persentase tutupan substrat terumbu karang telah di lakukan pada 3 (tiga) zona pengelolaan (zona perlindungan, pemanfaatan dan luar kawasan) Taman Nasional Karimunjawa. Metode penilaian terumbu karang skala luas Manta Tow diaplikasikan di sisi utara P. Bengkoang dan sisi selatan P. Cemara Besar (zona perlindungan), sisi selatan P. Bengkoang dan sisi utara P. Cemara Besar (zona pemanfaatan) dan luar kawasan (P. Seruni) untuk mengamati tutupan karang hidup, karang mati, pecahan karang dan karang lunak. Variasi persentase tutupan substrat dari 10-12 tarikan Manta Tow (panjang lintasan 200m) dari masing-masing sisi pulau telah membentuk pola spasial kondisi terumbu karang. Selanjutnya penilaian kondisi terumbu karang dikonfirmasi dengan menggunakan metode penilaian rinci UPT (Underwater Photo Transect) dengan satu stasiun setiap sisi pulau. Hasil menunjukkan terdapat perbedaan pola spasial kondisi terumbu karang yang ditunjukkan oleh perbedaan yang signifikan persentase tutupan karang hidup, karang mati, pecahan karang dan lifeform karang antar zona pengelolaan.  Kondisi terumbu karang di dalam kawasan lebih baik dan memiliki keragaman jenis karang lebih tinggi daripada di luar kawasan Taman Nasional Karimunjawa. Pola spasial kondisi terumbu karang dapat dijadikan indikator terjadinya gangguan pada ekosistem terumbu karang di suatu kawasan dan dapat digunakan untuk analisis data pemantauan terumbu karang secara berkala di kawasan konservasi.Kata Kunci: pola pasial, kondisi terumbu karang, manta tow, underwater photo transect, Taman Nasional Karimunjawa,